Komunikasi Pemasaran Ketok Tular Langsung (Direct Word of Mouth Marketing) Dalam Industri Restoran - Akil, Rafiuddin (FISIP IBI-K57 Prodi Komunikasi, 2020)
Culinery industry comes from tourism sector and it will be one of interested factor for people visited in a country. Restourant industry would be serve any thing for original of Indonesian culinary for unique and real cuisine. This research talk about the impact of Direct Word of Mouth for visited people to restaurant. The theoretical studies of this research is Word of Mouth Marketing dan Hierarcry of effect, marketing communication, interpersonal communication, Promotion and Publicity. This research studies in one of Batavian restaurant in Kuningan – Jakarta, and use quantitative methods to 70 respondents. Hipotetis testing in linear regretions. Finding research show that there are strongest impact from Direct Word of Mouth for visited people to restaurant (84,6%). The degree of Attentions was the level of the highest in hierarchy of effect for people if Direct Word of Mouth was implemented.